THE IMPLEMENTATION OF GUIDANCE SERVICES GROUP PLAY TECHNIQUE CAN ENHANCE STUDENTS' MOTIVATION IN CLASS X MAN PADANG YEAR STUDY 2014-2015 - Linda Fitria (Universitas Muhammadiyah Tapanuli Selatan, 2016)
The research is based on the problem of the low student motivation in the school environment and the general problem of this research is